Dinamika Kelompok Wanita Tani Mbanar Melalui Program Integrated Farming di Desa Kragan Kecamatan Gondangrejo Kabupaten Karanganyar - Muhammad Lanang Samudro; Retno Setyowati (AGRITEXTS: Journal of Agricultural Extension, 2023)
The Women Farmer Group is a community group that seeks training from stakeholders to promote economic growth. This research was necessary due to the Mbanar Women Farmer Group needed to gain the experience and knowledge to manage an integrated agricultural program. This research examines the dynamics of the Mbanar Women Farmer Group. Descriptive qualitative research is used at Gondangrejo Sub-district, Karanganyar Regency. This research uses purposive and snowball sampling for informant selection. The data utilized are primary and secondary from interviews, documentation and observation. Research shows that Mbanar Women Farmers Group dynamics involve group components, such as 1) The group goals in the category have not been achieved, 2) The group structure is in the good category, 3) The group task function is in a suitable category, 4) The development and coaching of the group is in the appropriate category, 5) Group cohesiveness in the good category, 6) Group pressure in the not appropriate category, 7) Group effectiveness in the adequate category, 8) Group atmosphere in the good category, and 9) Hidden intentions in forming groups in the appropriate category.